Negative ion crystal formation in nonequilibrium plasmas - Lapshin, V.I.; Maslov, V.I.; Onishchenko, I.N.; Stomin, V.L. (Вопросы атомной науки и техники, 2000)
The crystal formation of heavy negative ions is considered in following system. The plasma flow with positive ions and electrons propagates vertically up and extends in radial direction. The flow propagates relative to heavy negative ions, subjected to gravity. The flow excites the perturbations of large amplitudes. The properties and evolution of these excited perturbations are considered. The evolution equation is derived for the case of any amplitudes. It is shown that these perturbations of large amplitude lead to spatial ordering of heavy negative ions in nonequilibrium plasma.